Primary Caregiving as a Framework for Preparing Early Childhood Preservice Students to Understand and Work with Infants. Issue 3 (2nd April 2016) - Lee, Seung Yeon; Shin, Minsun; Recchia, Susan L.
ABSTRACT: Research Findings : This qualitative study explored the process through which a small group of preservice early childhood teachers engaged in primary caregiving as a framework for learning about early care and education with infants during an infant practicum course at a university-affiliated early childhood center in the United States. Based on multiple data sources, findings revealed that the participants found the primary care system to be beneficial to both infants and teachers. The student teachers gained a better understanding of the uniqueness of the infancy period, experienced the emotional rewards of a special relationship with an infant, and learned to provide individualized and relationship-based infant care and education, while the infants received the benefits of this care. The integration of hands-on practice enacting a primary care system in a responsive infant room, ongoing supervision, and a theory-to-practice seminar created an effective professional learning process for the student teachers, which helped them to grow as both infant teachers and early childhood professionals. Practice or Policy : These findings are a 1st step toward looking more deeply at 1 strategy as a promising practice for the future, offering implications for early childhood teacher education and new insight to the field.